Association of Metabolic Syndrome or Weather Conditions with the Severity and Prognosis of Sudden Sensorineural Hearing Loss - Yixi Xu; Yao Zhang; Qi Yan; Chen Chen; Bin Zhu; Ying Wang (Journal of International Advanced Otology)
BACKGROUND: It is reported that sudden sensorineural hearing loss (SSNHL) is closely related to diabetes, hypertension, and hyperlipidemia. While the metabolic syndrome (MetS) is a multifactorial disease that includes diabetes, hypertension, dyslipidemia, and obesity, which are known to be associated with SSNHL. Weather conditions have long been known to affect the SSNHL. This study aimed to make a clear connection between MetS, or weather conditions, and the severity and prognosis of SSNHL.